2004
DOI: 10.1159/000077126
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Renal Tuberculosis following Intravesical Bacillus Calmette-Guérin Therapy for Bladder Cancer

Abstract: We present a case of isolated renal tuberculosis following bacillus Calmette-Guérin (BCG) therapy for bladder cancer. In the presurgical radiographic examination, we suspected an atypical renal cell carcinoma. According to the diagnosis of renal cell carcinoma, we performed a radical nephrectomy. The histological findings were tuberculosis-specific inflammatory changes and the patient received an antituberculous multiple drug therapy for a year. It is concluded that we should pay attention to the possibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Except for two case reports by Rocha and Wada, all of the reported cases of renal granulomas presented with systemic constitutional symptoms of fever. [3][4][5][6][7][8][9][10][11][12]16,20 Perhaps the absence of fever in the two cases presented here could be related to the dose and strain of BCG used. Whereas in these two cases, 50 mg of BCG Tice strain was used, previous reports of febrile renal granulomas were reported with BCG Connaught strain 5,11,16 or BCG Tice strain at higher dose of 120 mg per installation.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Except for two case reports by Rocha and Wada, all of the reported cases of renal granulomas presented with systemic constitutional symptoms of fever. [3][4][5][6][7][8][9][10][11][12]16,20 Perhaps the absence of fever in the two cases presented here could be related to the dose and strain of BCG used. Whereas in these two cases, 50 mg of BCG Tice strain was used, previous reports of febrile renal granulomas were reported with BCG Connaught strain 5,11,16 or BCG Tice strain at higher dose of 120 mg per installation.…”
Section: Discussionmentioning
confidence: 75%
“…10,12,16 When analyzing available published case reports on renal granulomas, we found that most cases reported multifocality of renal granulomas with multiple renal masses on imaging studies, 4,8,[11][12]16 while others reported solitary renal foci. 5,7,9,10 Both patients in the present series had multiple renal granulomas. Another sign is the "central unaffected calyx sign" on delayed phase CT images that has been previously described in patient with a renal BCG granuloma.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Local side effects due to BCG administration are frequent (90%), and may include hematuria, and dysuria along with cystitis [ 3 ]. Various other local and systemic side effects such as acute respiratory failure and septic shock [ 4 ], hemolytic uremic syndrome, disseminated intravascular coagulation, sepsis, multi-organ failure [ 5 , 6 ], isolated renal tuberculosis (TB) [ 7 ], granulomatous hepatitis [ 8 , 9 ], peritonitis [ 10 ], pancytopenia, epididymo-orchitis [ 11 ], and diffuse granulomatous mesenteric disease [ 12 ] have also been reported. Steg et al described a 3% and Lamm et al around 0.7% incidence of BCG-related granulomatous hepatitis [ 3 , 13 ].…”
Section: Introductionmentioning
confidence: 99%